Screen of rice mutants in adversity of low-temperature during germination - JIN Jing; ZHU Cheng; FU Ya-ping; SUN Zong-xiu (浙江大学学报. 农业与生命科学版, 2003)
The screen of rice mutants in adversity of temperature out from a transposon Ac/Ds inserted rice transgenic population during germination was performed. Under low temperature, we observed the germination of seeds harvested in different years and found that the mutants (NO. T108A5 and T237bl) were higher than the control by approximate 50%. Germination relativity between the same seeds gained in two years demonstrated the method of screen mutants was available and further researches haves been going along.